Determination of Amino Acid Enantiopurity and Absolute Configuration: Synergism between Configurationally Labile Metal‐Based Receptors and Dynamic Covalent Interactions. Issue 49 (31st October 2013) - Scaramuzzo, Francesca A.; Licini, Giulia; Zonta, Cristiano
Abstract Reliable determination of the enantiomeric excess of free amino acids can be obtained by measuring the induced circular dichroism of a multicomponent assembly formed by a modified tris(2‐pyridylmethyl)amine ligand, a zinc salt, and the amino acid of interest. The systems furnish reliable information for all natural amino acids.